2014
DOI: 10.1007/s11071-014-1812-4
|View full text |Cite
|
Sign up to set email alerts
|

Hyperchaos in a 4D memristive circuit with infinitely many stable equilibria

Abstract: This paper studies a four-dimensional (4D) memristive system modified from the 3D chaotic system proposed by Lü and Chen. The new system keeps the symmetry and dissipativity of the original system and has an uncountable infinite number of stable and unstable equilibria. By varying the strength of the memristor, we find rich complex dynamics, such as limit cycles, torus, chaos, and hyperchaos, which can peacefully coexist with the stable equilibria. To explain such coexistence, we compute the unstable manifolds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(66 citation statements)
references
References 52 publications
0
66
0
Order By: Relevance
“…Due to the unique nonlinear characteristics of memristors [1], an explosive growth study of memristor based circuits has been boosted up in the past years [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Unfortunately, induced by technical handicaps in fabricating nanoscale memristor, the commercial memristor is not expected to be available in the near future.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the unique nonlinear characteristics of memristors [1], an explosive growth study of memristor based circuits has been boosted up in the past years [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Unfortunately, induced by technical handicaps in fabricating nanoscale memristor, the commercial memristor is not expected to be available in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, various kinds of physically implementable equivalent circuits which can manifest the three fingerprints of memristors [17] have attracted much attention [2,[6][7][8][9][10][11][12][13][14][15][16][17][18]. Popularly, the circuits implemented by operational amplifiers and analog multipliers [7][8][9][10][11][12] as well as the circuits consisting of diode bridge cascaded with RC [13][14][15], LC [16], and RLC [18] filters have been used for experimental measurements in memristor based circuits. The most significant feature of the memristive diode bridge emulators is ungrounded limitation, which makes it as a serial expandable and flexible element in designing memristor based circuit [19].…”
Section: Introductionmentioning
confidence: 99%
“…In [19], a memristive hyperchaotic real Lü system was firstly constructed by adding a flux-controlled memristor to a traditional Lü system, which can be described by:…”
Section: Generation Of Mhclsmentioning
confidence: 99%
“…He et al concluded the characteristics of this method, such as high accuracy, fast convergence, and less computer resources consumption [40]. Recently, Li et al proposed a new 4D hyperchaotic memristive circuit [41], which possesses abundant complex dynamics. The main feature of this system is having uncountable infinite number of stable equilibria, which is significantly different from other reported chaotic systems before.…”
Section: Introductionmentioning
confidence: 99%